2021
DOI: 10.3390/jpm11010027
|View full text |Cite
|
Sign up to set email alerts
|

Blood Biomarkers for Assessing Headaches in Healthcare Workers after Wearing Biological Personal Protective Equipment in a COVID-19 Field Hospital

Abstract: The coronavirus disease 2019 (COVID-19) has led to a pandemic, which among other things, has highlighted biosafety as a key cornerstone in the management of disease transmission. The aim of this work was to analyze the role played by different blood biomarkers in predicting the appearance of headaches in healthcare workers wearing personal protective equipment (PPE) in a COVID-19 treatment unit. A prospective cohort study of 38 healthcare workers was performed during April 2020. Blood analysis, performed just … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…10 Among the analyzed parameters, creatinine was found to be significantly elevated in individuals who developed headaches after 4 hours of use of PPE compared to individuals who did not (p = 0.019 ). 10 In addition to headaches, the included studies also pointed to psychosocial and work-related effects. Agarwal et al observed the presence of excessive sweating (100%), fogging of glasses, (88%) suffocation (83%), shortness of breath (61%), fatigue (75%), and pressure marks on the skin (19%) in individuals after prolonged use of PPE.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…10 Among the analyzed parameters, creatinine was found to be significantly elevated in individuals who developed headaches after 4 hours of use of PPE compared to individuals who did not (p = 0.019 ). 10 In addition to headaches, the included studies also pointed to psychosocial and work-related effects. Agarwal et al observed the presence of excessive sweating (100%), fogging of glasses, (88%) suffocation (83%), shortness of breath (61%), fatigue (75%), and pressure marks on the skin (19%) in individuals after prolonged use of PPE.…”
Section: Resultsmentioning
confidence: 89%
“…7,8 Zaheer et al found a mostly bilateral (69%), pressure (45.5%) and moderate intensity (69%) pattern in new headaches.8 Furthermore, individuals previously suffering from headaches have been identified with increased susceptibility to headache induction by EPI. 8,9 Martín-Rodríguez et al 10 analyzed possible biomarkers in the prediction of head- External compression headache during Covid-19 pandemic: a neglected entity aches associated with the use of PPE. 10 Among the analyzed parameters, creatinine was found to be significantly elevated in individuals who developed headaches after 4 hours of use of PPE compared to individuals who did not (p = 0.019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous epidemic of SARS, protective gear-induced health hazards led to the suboptimal use of the N-95 mask [ 11 , 12 ]. In the recent pandemic era, protective gear-related occupational hazards have not been well addressed and quantified in the scientific literature, despite the significant suffering of physicians and other HCWs reported by some small-scale studies conducted in different parts of the world [ 13 15 ]. To date, there have been no such studies in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been no such studies in Bangladesh. The reported hazards include headache, skin breakdown, rash, impaired cognition, sweating, dry mouth, and dyspnea [ 13 15 ]. The prevalence of hazards ranged from 66–72% in different studies [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%